Assessment of the long-term impact of chess lessons in preschool age on the further development of logical thinking and academic success - Shymanskyi, Oleksandr (Педагогічна Академія: наукові записки, 2025)
Logical thinking is integral to a person’s cognitive development. It allows them to process information clearly and consistently, helping them conclude, understand why certain events occur, and find solutions to problems. The article aimed to investigate the impact of chess training in preschool on developing logical thinking and children’s academic success in later education. Methods. To achieve this goal, the following theoretical methods were employed: analysis of scientific sources, comparative analysis, methods of generalization, and systematization of knowledge regarding the role of chess in children’s cognitive development. Results. The study revealed that logical thinking is one of the key components of cognitive development, determining a person’s ability to process information rationally and in a structured manner. The primary characteristics of logical thinking include consistency, objectivity, and reliance on evidence. Developing logical thinking is considered one of the priority areas in forming the intellectual potential of preschool children. Among the most common means to achieve this objective are various types of games (competitive games, role-playing games, board games), puzzles, construction sets, and programming tools. Specific characteristics distinguish each of the listed means and have the potential to influence the formation of logical thinking. A comparative analysis of approaches to the formation of logical thinking has shown the high effectiveness of chess classes, which occupy a leading place among other methods of intellectual development. Unlike puzzles or construction sets, chess requires the child to solve problems and consider the consequences of their actions, predict the opponent’s moves, and adapt their strategy in real time. Implementing innovative approaches to chess education that align with modern educational trends and consider preschoolers’ age-specific characteristics is becoming particularly relevant. One such approach is the use of interactive digital platforms that combine play, learning, and technology. An effective tool for organizing systematic chess lessons within the digitalization of preschool education is Gambitius. This platform merges the classic chess game with a vibrant interface that fosters logical thinking in an interactive environment. Conclusions. Thus, the systematic integration of chess into preschool education, particularly through digital technologies, can be a powerful instrument for developing children’s intellect, ensuring a seamless transition from preschool to primary education, and promoting future educational success.